Christian citizens in an Islamic state the Pakistan experience - Gabriel, Theodore P. C. (Ashgate Pub., 2007)
Christian Citizens in an Islamic State deals with the important question of inter-faith relations in Pakistan, a vital region of the Islamic world which has been the scene of the rise of both Islamic militancy and partnership with the West in counter-terrorism measures.Theodore Gabriel clarifies the history of Christian-Muslim relations in the region, explores the rise of Islamic militancy, and draws on personal interviews to determine the mind set of both Christians and Muslims in Pakistan today.